Study of Correlation of Neonatal Outcomes with Gross Abnormalities of Placenta and Umbilical Cord - Nair, Bindu T; Raju, Uma (Journal of Nepal Paediatric Society, 2018)
Introduction: Perinatal outcome of new-borns is greatly influenced by abnormalities of placenta and umbilical cord. In most of the deliveries, whether home or institutional, the placenta and umbilical cords are discarded without examination. Due to paucity of information on abnormalities of placenta and cord, there is hardly any correlation with foetal outcomes. The aim was to study the correlation between the foetal outcome and the different types of abnormalities of placenta and umbilical cord. Materials and Methods: A prospective, cross-sectional, descriptive, randomised study was conducted from January 2016 to December 2016 in a tertiary care hospital in North India. The study was carried out on 1000 term singleton newborns. The placenta and umbilical cords were obtained from both normal and caesarean section deliveries. A proforma was used to gather data from the patients and new-borns. Statistical analysis was done using Statistical Package for the Social Sciences (SPSS) version 20 (SPSS Inc, Chicago, IL, IBM version) along with Microsoft Excel (2010 version). Results: One thousand placentae and umbilical cords were examined of which high placental weight/birth weight ratio, gross anomalies of placenta (infarctions, calcifications and retro placental haematoma), marginal (battledore and velamentous) umbilical cord insertions, long umbilical cords and single umbilical artery were associated with negative foetal outcomes. Conclusions: There was a high incidence of adverse foetal outcome with placental and umbilical cord abnormalities. Education of our health personnel dealing with deliveries on the importance of proper examination of the placenta and umbilical cords should be emphasised and instituted upon.